2018
DOI: 10.1126/sciimmunol.aau2125
|View full text |Cite
|
Sign up to set email alerts
|

The probacterial effect of type I interferon signaling requires its own negative regulator USP18

Abstract: Type I interferon (IFN-I) signaling paradoxically impairs host immune responses during many primary and secondary bacterial infections. Lack of IFN-I receptor reduces bacterial replication and/or bacterial persistence during infection with several bacteria. However, the mechanisms that mediate the adverse IFN-I effect are incompletely understood. Here, we show that Usp18, an interferon-stimulated gene that negatively regulates IFN-I signaling, is primarily responsible for the deleterious effect of IFN-I signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…It is possible that USP18 may also involve other USPs and suppress TNF-α in different pathways. Such a relationship was described for USP20 which deubiquitinates mitochondrial adaptor protein STING (stimulator of interferon genes) Shaabani et al, 2018). However, other authors have shown that this recruitment, leading to STING stabilization, sustains cellular antiviral responses and decreases susceptibility to HSV-1 .…”
Section: Infectionsmentioning
confidence: 87%
See 3 more Smart Citations
“…It is possible that USP18 may also involve other USPs and suppress TNF-α in different pathways. Such a relationship was described for USP20 which deubiquitinates mitochondrial adaptor protein STING (stimulator of interferon genes) Shaabani et al, 2018). However, other authors have shown that this recruitment, leading to STING stabilization, sustains cellular antiviral responses and decreases susceptibility to HSV-1 .…”
Section: Infectionsmentioning
confidence: 87%
“…IFNAR1 or Usp18 knock-out CD11c-Cre+ cells were observed to mitigate bacterial titres in several organs and to prolong survival. This phenomenon was proven to be independent of the IFNAR2 binding and isopeptidase domains (Shaabani et al, 2018). It is possible that USP18 may also involve other USPs and suppress TNF-α in different pathways.…”
Section: Infectionsmentioning
confidence: 92%
See 2 more Smart Citations
“…Type I interferon (IFN-I) is one of the first cytokines induced during viral infection and plays an essential role in orchestrating effective immune responses due to its induction of antiviral genes and as an immune stimulant promoting cytokine/chemokine production, upregulating activation receptors, recruiting immune cells to infected tissues and facilitating optimal antigen presentation to T cells (McNab et al, 2015). Despite the central role of IFN-I in promoting an antiviral state, deleterious consequences of IFN-I signaling during viral infection have been reported (Ng et al, 2015; Shaabani et al, 2018; Teijaro et al, 2013; Wilson et al, 2013). An elevated IFN-I gene signature correlates with disease severity following influenza virus, lymphocytic choriomeningitis virus and severe acute respiratory syndrome (SARS)-Coronavirus (SARS-CoV) infections (Baccala et al, 2014; Channappanavar et al, 2016; Davidson et al, 2014; Davidson et al, 2015; Teijaro, 2016; Teijaro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%